2019
DOI: 10.1212/nxi.0000000000000590
|View full text |Cite
|
Sign up to set email alerts
|

Long-term safety and efficacy of subcutaneous immunoglobulin IgPro20 in CIDP

Abstract: ObjectiveTo investigate the long-term safety and efficacy of weekly subcutaneous IgPro20 (Hizentra, CSL Behring) in chronic inflammatory demyelinating polyneuropathy (CIDP).MethodsIn a 48-week open-label prospective extension study to the PATH study, patients were initially started on 0.2 g/kg or on 0.4 g/kg weekly and—if clinically stable—switched to 0.2 g/kg weekly after 24 weeks. Upon CIDP relapse on the 0.2 g/kg dose, 0.4 g/kg was (re)initiated. CIDP relapse was defined as a deterioration by at least 1 poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
64
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(71 citation statements)
references
References 23 publications
7
64
0
Order By: Relevance
“…Overall, patients who were treated with the more frequent lower IVIg dose schedule did not show more exacerbations. This suggests that high IgG peak levels are not needed for successful IVIg maintenance treatment, and this finding is in accordance with previous studies that showed SCIg could be used as maintenance treatment for CIDP [38,43]. As high peak serum IgG levels are not needed during maintenance IVIg treatment of CIDP, more personalized IVIg treatment schedules are preferred over treating all patients with expensive high maintenance dosages such as 1 g/kg every 3 weeks [44].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Overall, patients who were treated with the more frequent lower IVIg dose schedule did not show more exacerbations. This suggests that high IgG peak levels are not needed for successful IVIg maintenance treatment, and this finding is in accordance with previous studies that showed SCIg could be used as maintenance treatment for CIDP [38,43]. As high peak serum IgG levels are not needed during maintenance IVIg treatment of CIDP, more personalized IVIg treatment schedules are preferred over treating all patients with expensive high maintenance dosages such as 1 g/kg every 3 weeks [44].…”
Section: Discussionsupporting
confidence: 87%
“…This might be attributable to the stable situation of the patients or mean that adverse events may not be caused by peak serum IgG levels, as has been previously suggested [37]. The long-term safety and efficacy of subcutaneous immunoglobulin (SCIg) in CIDP has been established (PATH trial) [38]. SCIg is generally given more frequently and in lower dosages than IVIg, similar to the comparison of treatment schedules in our trial.…”
Section: Discussionsupporting
confidence: 73%
“…In the PATH extension study, patients who did not experience a relapse had mean change‐scores close to 0 in all measures, indicating stability as a group. However, the range of change was wide, and some patients improved by 28 centile points in the R‐ODS, by 19 points in the MRC sum score, and by 29 kPa in grip strength . Findings in the study by Cirillo et al are in keeping with the PATH extension study, providing evidence of a subpopulation of CIDP patients with continuous improvement.…”
mentioning
confidence: 54%
“…The extension study to the PATH trial demonstrated the long-term efficacy of SCIG and other advantages of SCIG Mr. Brown could have received such as increased independence, less time spent during subcutaneous treatment, and less felt side effects when compared with IVIG. 11 Had first-rate clinical decision science been implemented with regards to Mr. Brown's treatment he may have been offered something more compatible with his needs as a whole and not just for his medical needs.…”
Section: New Knowledge Related To Clinical Decision Sciencementioning
confidence: 99%